Gemi yapılarında gerilme yığılması öngörülerinin kaba ağ yapısı ve makine öğrenmesi ile gerçekleştirilmesi - Ateş, Burçin (Fen Bilimleri Enstitüsü, 2020)
Gemi ve deniz yapılarının tasarımında dikkate alınması gereken limit durumlar vardır. Servis limit durumunda (SLD) global ölçekte ve kaba ağ yapısıyla analizler yapılır. Yorulma limit durumunda (YLD), SLD'nda gözükmeyen ve yapının özellikle süreksizlikler veya ani değişim gösteren bölgelerinde bulunan gerilme yığılmalarına ve bu gerilmelerin yorulma ömrüne olan etkisine yoğunlaşılır. Sıcak nokta gerilmesi denilen ve sonlu elemanlar analizi ile ekstrapolasyon kullanılan hesap yaklaşımında, yapının yerel ve SLD'de kullanılana kıyasla çok daha yüksek çözünürlükte bir ağ yapısının kullanıldığı bir model üretilir. Bu modelin analiz süresi, ağ yapısı ve farklı yükleme durumlarının da katkısıyla yüksek hesaplama maliyetlerine yol açmaktadır. Bu durum özellikle tasarım için gerekli parametrik çalışmaların pratikte yapılmasını zorlaştırmaktadır. Makine öğrenmesi, genel bir matematik model kullanımı yerine, deney yoluyla elde edilen veya karmaşık matematiksel modellerden üretilen verilerden yola çıkılarak kurulan yaklaşık modellerin anlam çıkarma, tahmin gibi amaçlarla kullanılmasını sağlayan istatistiksel yöntemleri ifade eder. Gerilmeler, yapısal mekanik analizlerin çoğunda incelenir. Yorulma dayanımını etkileyen faktörlerden bazıları, malzeme tipi, ortalama ve artık gerilme, kalite ve kaynak kusurları gibi imalat faktörleri ve son olarak boyut ve plaka kalınlığı dır. Yorulma, yeterince yüksek bir güvenlik seviyesi sağlamak için gemilerde önemli bir tasarım kriteridir. Bir yapıda şekil veya kesitte ani bir değişiklik olan bölgeler süreksizlik nedenidir ve gemi söz konusu olduğunda kabaca birçok yapının birleşimi olduğu düşünülürse bu tarz süreksizlikler kaçınılmazdır. Çeşitli konumlardaki (örn. ambar kapağı köşelerinde, kaynak ağızlarında, perdelerde, takviye uçlarında, kiriş ağ plakalarında ve çift dipli sintine alanlarında, enine stifner bağlantılarında..vb) gerilme yığılmaları nedeniyle yorulma meydana gelir. Bu tür gerilme yığılmalarının değerlendirmesi yapısal tasarımda normal gerilme analizinden farklıdır. Buradaki amaç akma gerilmesinden ziyade süreksizlik bulunan noktada lokal bir değerlendirme yapıp yorulma nedeniyle oluşan kırılma ve çatlama gibi durumların değerlendirilmesidir. Gemi yapılarında enine stifner bağlantıları veya T birleşim noktaları gibi çeşitli kaynaklı bölgelerde gerilme yığılmaları meydana gelir. Bu bölgelerden klas kuruluşları da incelendiğinde çok sık karşılaşılan bir problem olan, T şeklinde iki plakanın birleşiminden oluşan yapısal bir modelin gerilme yığılmaları bu çalışma kapsamında incelenmiştir. Modelin simülasyonu Ansys APDL Script programlama dilinde parametrik model kodu oluşturularak yapılmıştır. Seçilen bağımsız parametreler ile modelin boyutu, kalınlığı, yük durumu ve mesh boyutları düzgün dağılımlı rastgele değişmektedir. Aynı zamanda değişen parametrelerin sınırları gemi inşa alanında kullanılmaya uygun olacak şekilde genişletilmiştir. Böylece modelin çok değişkenli birden fazla durumunu gözlemek mümkün olmuştur. Modelde gemi dizaynı sırasında uyulması gerekilen klas kuruluşlarının belirlediği kurallara göre yapılan gerilme hesaplaması referans değerler olarak kabul edilmiştir. Bu gerilme hesaplamalarında plakaların kalınlığı kadar (t x t) hassas bir mesh örgüsü uygulanıp gerilme değerleri elde edilmiştir. Sonra aynı model mesh hassasiyeti azaltılarak daha kaba bir mesh ile analiz edilmiştir. Yapılan analizlerde önce 200 farklı durum incelenmiş olup sonra veri sayısı arttırılarak 2000 farklı analiz yapılmıştır. Kaba ağ yapısına sahip modelden çekilen gerilme değerleri (aynı zamanda modeldeki gerilme yayılımını ölçmek için meta parametre olan) bir yarıçap kadar alanda taratılmıştır. Alan etkisi önemli bir parametredir. Çünkü yığılmanın meydana geldiği noktadan iki farklı yarıçap parametresi ile uzak ve yakın alanlardan mantıklı gerilmeler alınarak, etkisiz noktalardaki değerlerin modelde oluşturacağı sapmaların önüne geçilmiştir. Taratılan alanda oluşan gerilme dağılımının ortalaması ve standart sapması da makine öğrenmesi uygulaması için bir girdi oluşturacaktır. Amaç, kaba bir mesh analizinden elde edilen gerilmelerin dağılımı, varyansı, mesh boyutu, maksimum gerilmesi gibi farklı farklı etmenler ile makineye problemi öğretip referans gerilme değerini tahmin etmektir. Bu çalışma ile seçilen parametrelerin tahminde etkili olduğu gözlenmektedir. Örneğin mesh boyutunu makine öğrenmesi inputlarından çıkarıldığında kök ortalama kare hata dikkate alınırsa 2 kat artmaktadır, veya her iki model için ekstrapole edilmiş gerilme değerleri yerine maksimum gerilme değerlerine göre hata hesaplandığında yine 1,7 kat artış gözlemlenmektedir. Hesaplanan hata oranları makine öğrenmesi yöntemlerinden Gauss süreci regresyon analizi sonucunda elde edilen değerlerdir. Sonuç olarak, bir regresyon analizi yapılarak hassas mesh modelinin gerilme sonuçları tahmin edilmekte ve böylece büyük ölçekli yapıların tasarımında zaman ve bilgi tasarrufu sağlanmaktadır.

Stress is studied in most structural mechanical analyzes. Ship structures are inclined to fatigue due to the high cyclic loading caused by waves, as well as changing cargo distributions and exciting vibrations. Apart from these, other factors are affecting fatigue strength such as; material type, average and residual stress, quality and welding defects of manufacturing factors, and size and plate thickness. Fatigue is an important design criterion for ships to provide a sufficiently high level of safety. Regions with a sudden change in shape or cross-section in a building are the cause of discontinuity, and such discontinuities are inevitable when the ship is considered to be a combination of many structures. Cracking occurs due to stress build-up in various locations (e.g. hatch cover corners, weld mouths, curtains, stiffener ends, beam web plates and double bottom bilge areas, transverse stiffener connections, etc.). The evaluation of such stress concentrations differs from the normal stress analysis in structural design. It is important to make a local assessment at the point where there is discontinuity rather than yield stress and to evaluate the conditions such as breakage and cracking caused by fatigue. Using the finite element method, stress concentrations that may occur in the discontinuities in the ship structure are calculated due to internal loads such as bending moments and shear forces. Multi-node mesh structure (fine mesh) is required for analysis of regions with stress concentrations such as a source or the perimeter of a crack in local calculations. Calculations on this subject require fine mesh, which is a very time-consuming analysis, it is also disadvantageous in terms of the space it takes up on the computer. For example, in the thesis work, the analysis time started with a fine mesh structure for 2000 data lasted 5 and a half hours, and the analysis with a rough mesh structure took only 35 minutes. In the study to be performed, the goal is to calculate with a coarse mesh, to reach usable results without the need to calculate with a fine mesh. At the same time, this will be considered as an optimization problem and applications will be made. Thus, the scope of application of shell finite element analysis will be expanded to further improve local approaches. Stress concentration occurs in various welded areas such as transverse stiffener joints or T junctions in ship structures. When class institutions are also examined, the stress concentrations of a structural model consisting of two T-shaped plates, which is a very common problem, are investigated within the scope of this study. The simulation of the model was done by creating parametric model code in Ansys APDL Script programming language. Randomly distributed properly independent parameters are selected as; base plate thickness, top plate thickness, base plate width, base plate aspect ratio, top plate aspect ratio, mesh size random values, force in the x direction, force in the y direction, force in the z direction. The change interval of parameters is respectively; 10 - 40 mm (thickness), 1 - 4 m (width), 1.2 - 2 (aspect ratio), 0 - 1 (mesh size), 6.00E+02 - 6.00E+04 N (forces). The force limits are chosen in this way to ensure that the maximum stress range is spread from 2,8 MPa to 280 MPa. Because of the observing all possible multivariate states of the model, the limits of the other independently changing parameters have been extended to be general usage in the shipbuilding area. Stress calculations made according to the rules determined by the class organizations that should be followed during the ship construction are accepted as reference values. In these stress calculations, a mesh is applied to the model as much as the thickness of the plates (t x t) and stress values are obtained. Then, the same model analyzed again with a coarser mesh, reducing mesh sensitivity. For fine mesh, (t x t) is used as the plate thickness, while coarse mesh is used in the mesh size in the range of (3t x 3t) - (5t x 5t). The structure is held on all four sides, it does not have a free edge. So there are restrictions on displacement in the x, y, z directions. The applied forces, on the other hand, were created in the middle of the upper plate using the mpc_gen function, and the main node was created and transmitted to other points. Mpc represents the multipoint restriction elements used to find node forces. These analyzes first examined 200 different situations and then 2000 different situations were investigated to observe the effect of the increase in the number of data. As a result of the analysis, each node coordinate, principal and von mises stresses were taken as an array format from the Ansys package program. In the data discovery and cleaning step following the data collection step, the data of the model whose simulation is completed with the Ansys program and the output values are obtained will be done with the help of the Python program. A filtering operation will be carried out over the recorded stress values and node positions for each data set. Filtering was done over the node where the maximum von mises stress occurred. The stress values taken from the model consisting of few nodes are also scanned in a field up to a radius which is the meta parameter to measure the stress spread in the model. Filtering effect is an important parameter. Because two different radius parameters from the point where the accumulation occurs, sensible stresses are taken from distant and close areas, and deviations from the values in ineffective points in the model are prevented. The mean and standard deviation of the stress distribution in the scanned area will also be an input for the machine learning application. Machine learning is defined as usage algorithms and calculation statistics to learn data from them without being explicitly programmed. The variables (numerical or categorical) are evaluated and an output is presented to estimate the problem. It is a subdivision of the artificial intelligence field in computer science. Today, machine learning has come to the fore, abundance of data, more efficient data storage and faster computers. There are many different ways to enable a computer to learn from data, which can be divided into four main subdivisions of machine learning: supervised learning, unsupervised learning, semi-supervised learning and reinforcement learning. Common algorithms in supervised learning include logistic regression, bayesian approach, support vector machines, neural networks and random forests. In both regression and classification, the aim is to find specific relationships or structures that allow us to effectively produce the correct output data in the input data. Noisy or incorrect data labels will clearly reduce the effectiveness of the model. Model complexity refers to the complexity of the function that is tried to learn, similar to the degree of polynomial. The appropriate level of model complexity is usually determined by the quality of the training data. If you have a small amount of data or your data is not evenly distributed in different possible scenarios, a low complexity model should be preferred. The Gaussian process regression (GPR) is a nonparametric Bayesian approach to regression that fluctuates in machine learning which are selected for the problem. There are several benefits that GPR works well in small data sets and can provide uncertainty measurements on estimates. The Bayesian approach determines a probability distribution on all possible values. In this approach, we see the parameters as random variables distributed before. Other guided learning methods also learn exact values for each parameter. Calculates the probability distribution on all acceptable functions suitable for GPR data. Machine learning algorithm was applied by using scikit-learn, numpy, pandas libraries in python program. Data has 6 input values for x values; mesh size, the standard deviation of the strains filtered according to the parameter r1, the average of the strains filtered according to the parameter r1, the standard deviation of the values filtered according to the parameter r2, the average of the values filtered according to the parameter r2, the extrapolated tension value obtained from the coarse mesh results. For the y value, 1 output value is assigned to the extrapolated stress value obtained from the fine mesh results. Values are classified as 20% test and 80% training data. After the data are separated as training and test data, the selected kernel function is defined. Kernel functions depend on the individual's choice, and in this problem, since the Gauss process will be regressed, the radial based kernel (RBF) function has been preferred. Other kernel functions were also tried and it was preferred to use a single kernel coefficient instead of multiple kernels. It is the radial basis function (RBF) kernel used in this equation, encoding the smoothness of functions, where the similarity of the inputs in space corresponds to the similarity of the outputs. The two parameters of this kernel are the length scale (l) and the lower and upper limit on this scale, respectively. If these limits are set to fixed, the length scale cannot be changed during the hyper parameter setting. If the data type is float, isotropic kernel and array is anisotropic kernel. After the kernel function is selected, the Gauss process regression model is assigned with Scikit-learn. In the data set, x values and y values are scaled differently. Standard scalar conversion is applied to input values, and power transformation is applied to output value. Yeo-johnson method, which is one of the power transformations, was chosen because it produces more compatible data compared to other methods. After the model fit, y values were estimated according to the x values in the test data. Values converted by transformation were restored to their true size by inverse transformation. In order to measure the quality of estimates, the metric systems module in the scikit-learn library is based on and more than one method is applied. The aim is to teach the machine the problem by estimating the reference stress value with different factors such as distribution, variance, mesh size, maximum stress of the stresses obtained from a rough mesh analysis. It is observed that the parameters selected with this study are effective in estimating. For example, when the mesh size is removed from the machine learning inputs, the root mean squared error increases 2 times, or when error is calculated according to maximum stress values instead of extrapolated stress values for both models root mean squared error again 1.7 times increase is observed. The calculated error rates are the values obtained as a result of the Gaussian process regression analysis, which is one of the machine learning methods. Consequently, the strain results of the fine mesh model are estimated by performing a regression analysis without the need for fine mesh analysis, thus time and information are saved in the design of large-scale structures.
The forecasting of stress concentration in ship buildings by using rough mesh structure and machine learning method
Tez (Yüksek Lisans)-- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2020
Keywords: Gemi yapıları, Makine öğrenmesi; Ship buildings, Machine learning